FAKTOR PEMBENTUK HARGA JUAL PRODUK CPO ASAL INDONESIA - Intanna, Affinuta Vena; Yusuf, Himawan (JURNAL PERSPEKTIF BEA DAN CUKAI, 2019)
This study aims to analyze and obtain empirical evidence about the main factors forming the price of one of Indonesia's main export commodities, Crude Palm Oil (CPO). The data of this study are all data of CPO exports subject to export duty from January 2009 to June 2015. The analysis technique used in this study is multiple regression analysis using Eviews 8. Based on the results of the analysis, it can be concluded that the export duty, export standard prices, and international market prices have a positive and significant effect on CPO selling prices, while the inflation rate does not significant effect on CPO selling prices. Based on standardized coefficients, it can be concluded that international market prices have the strongest influence on CPO selling prices